2012
DOI: 10.1103/physrevd.85.044057
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting spacetimes of any dimension using geodesic deviation

Abstract: We present a general method which can be used for geometrical and physical interpretation of an arbitrary spacetime in four or any higher number of dimensions. It is based on the systematic analysis of relative motion of free test particles. We demonstrate that local effect of the gravitational field on particles, as described by equation of geodesic deviation with respect to a natural orthonormal frame, can always be decomposed into a canonical set of transverse, longitudinal and Newton-Coulombtype components… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 147 publications
(286 reference statements)
0
83
0
Order By: Relevance
“…We will now briefly review the aforementioned decomposition of the Weyl tensor in d spacetime dimensions [35,36], and then apply it to the concrete metric that we are interested in. In this section, capital Latin indices A, B, .…”
Section: Interpretation Of Weyl Componentsmentioning
confidence: 99%
“…We will now briefly review the aforementioned decomposition of the Weyl tensor in d spacetime dimensions [35,36], and then apply it to the concrete metric that we are interested in. In this section, capital Latin indices A, B, .…”
Section: Interpretation Of Weyl Componentsmentioning
confidence: 99%
“…In our recent work [6] we demonstrated that the equation of geodesic deviation, which describes relative motion of nearby free test particles, can in any D-dimensional spacetime be expressed in the invariant form…”
Section: Geodesic Deviation In An Arbitrary Spacetimementioning
confidence: 99%
“…known from the D = 4 case [4,6]. In equations (21), (22), only the "electric part" of the Weyl tensor represented by the scalars in the left column of (23) occurs, and there are various constraints and symmetries, for example…”
Section: Geodesic Deviation In An Arbitrary Spacetimementioning
confidence: 99%
“…For their metrics one has two classes of physically distinguished and analytically simple timelike geodesics: radial and circular (if exist) ones. Staticity not only considerably simplifies all calculations, moreover it allows for a physically meaningful notion of rest 1 . In an SSS spacetime we introduce three twins: twin A remains at rest on a non-geodesic worldline, twin B revolves on a circular orbit (geodesic or not) around the centre of spherical symmetry and twin C moves upwards and downwards following a radial geodesic.…”
Section: Introductionmentioning
confidence: 99%
“…In the local problem one considers a bundle of nearby (infinitesimally close) timelike curves and seeks for the longest one in the bundle. Again it is well known that there is a well defined procedure for solving the local problem in terms of the curvature tensor, which physically determines the behaviour of geodesic worldlines of nearby free test particles both in four and in a larger number of spacetime dimensions [1]. A locally maximal timelike curve is always a geodesic and is determined by solving the geodesic deviation equation.…”
Section: Introductionmentioning
confidence: 99%